Keratitis-Ichthyosis-Deafness (KID) Syndrome, case report - Tomasz Wasyłyszyn; Katarzyna Borowska (Our Dermatology Online, 2017)
Keratitis-Ichthyosis-Deafness (KID) syndrome is a congenital disorder characterized by keratitis, ichthyosis, and deafness. Authors present a 10 year old by with KID syndrome. The diagnosis was based on a clinical picture, hearing evaluations and genetic research.